Subtle Allegory within the Sacred Text: Political Motivations behind the Ramayana Manuscript in the 16th-17th Century CE Mughal Empire - Abednego Andhana Prakosajaya (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The Ramayana manuscript is well-known as a text embedded with prominent Hindu religious values. On various occasions, illustrations are added as a visual form that facilitates the narrative of the existing text. This phenomenon is seen in the Ramayana manuscript produced by order of the Emperor, local rulers, also known as Rajputs, or high officials during the Mughal period, where political dynamics are reflected in the manuscript's Illustrations produced in the royal court environment. This paper will use an iconological method that combines a comprehensive formal analysis of an illustration with an understanding of the contemporary socio-political context of the work's creation period. This study found that the depiction of the background, characters, and buildings in the Mughal Empire Ramayana Manuscript is filled with subtle allegorical elements rich in political satire. This work asserts that the Ramayana has a dual position: functioning primarily as a source of wisdom yet subtly hiding an allegorical message corresponding to the context of its creation reflected in the text's visual illustrations.